Strategies to Improve Teacher Performance through Transformational Leadership, Personality, Job Satisfaction, and Trust: A Path Analysis and SITOREM Study - Ila Nafilah; Rita Retnowati; Widodo Sunaryo (MASI Mandiri Edukasi, 2026)
Teacher performance remains a critical issue in improving the quality of education in Indonesia, particularly in private junior high schools. Previous studies have generally examined transformational leadership, personality, job satisfaction, and trust separately, with limited integration of these variables into a comprehensive model of teacher performance improvement. In addition, studies applying the Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) approach to determine priority improvement indicators are still limited. Therefore, this study aims to analyze the influence of transformational leadership, personality, job satisfaction, and trust on teacher performance and to formulate strategies for improving teacher performance through SITOREM analysis. This study employed a quantitative survey method using path analysis and SITOREM analysis. The sample consisted of 114 permanent foundation teachers from 32 private junior high schools accredited at the “B” level across seven sub-districts in Bogor Regency, West Java. The results indicate that transformational leadership, personality, job satisfaction, and trust have significant direct effects on teacher performance. Job satisfaction and trust also function as mediating variables in strengthening the influence of transformational leadership and personality on teacher performance. The SITOREM analysis identified several indicators that should be maintained, including work quality, productivity, punctuality, responsibility, supervision, and integrity, while indicators such as work efficiency, promotion opportunities, emotional stability, and environmental trust require priority improvement. The novelty of this study lies in integrating organizational and psychological variables with the SITOREM approach to formulate priority-based strategies to improve teacher performance. The findings are expected to make theoretical contributions to educational management research and to offer practical recommendations for school principals, supervisors, and policymakers to improve teacher performance and educational quality.